PENERAPAN MODEL PEMBELAJARAN GALLERY WALK PADA MATERI PROGRAM LINIER UNTUK MAHASISWA CALON GURU - Alip Rahmawati Zahrotun Nisa; Abd. Qohar (FMIPA UNIVERSITAS NEGERI MALANG, 2020)
This study aims to describe the response of student teacher candidates to learning using the Gallery Walk method on linear program material. The method used is to apply the Gallery Walk model in the VC class of Malang State University, amounting to 29 participants in one meeting, and collecting the participants' opinions with a response sheet that will be filled out by participating students. The results show that the participants are interested in using the Gallery Walk model but they feel that the use of the Gallery Walk model does not help participants to remember the material for a long period of time.